AB0208 FMD, VEGF, and IL-6 in VEDOSS Patients: the Precocity of Endothelial Dysfunction. (10th June 2014) - Bosello, S.L.; Canestrari, G.; Capacci, A.; Di Giorgio, A.; De Luca, G.; Bocci, M.; Parisi, F.; Berardi, G.; Rucco, M.; Alivernini, S.; Santoliquido, A.; Ferraccioli, G.
Abstract : Background: Endothelial dysfunction is a key feature of systemic sclerosis (SSc) and the involvement of the microvasculature is one of the earliest features of the disease. Recent new criteria for very early diagnosis of systemic sclerosis (VEDOSS) have been proposed. Objectives: The aim of this study was to investigate brachial artery endothelial-dependent flow-mediated dilation (FMD), IL-6 and VEGF levels in patients with primary Raynaud's phenomenon (RP) and SSc. Methods: In this study we enrolled 59 patients: 10 VEDOSS patients fulfilling the proposed VEDOSS criteria, 28 SSc patients fulfilling the 1987 ACR criteria, 11 gender and age matched healthy individuals as first control group and 10 gender and age matched primary RP patients with normal capillaroscopic findings as the second control group. Demographic, clinical and immunological parameters have been collected at the beginning of the study. Ultrasound assessment of FMD was performed in all RP subjects and in healthy subjects to evaluate endothelial dysfunction. VEGF, VEGF-RII, IL-6 and IL-6R plasma were determined by ELISA. Results: Scleroderma patients showed a reduced FMD (5.8±4.7%) compared to healthy controls (18.9±6.7%) (p<0.0001), and to subjects with RP (1.6±5.6%), (p=0.001). FMD of scleroderma patients and VEDOSS patients was comparable (6.6±3.8%). VEDOSS patients showed values of FMD significantly compromised compared to those of RP (p=0.05) and healthy controls (p<0.001). Finally, patients with primitive RP showed reduced FMD values compared to healthy controls (p=0.008). The values of FMD correlated inversely with disease duration (r=-0.46, p=0.004) and directly with the levels of KCO (r=0.47, p=0.007). The plasma levels of VEGF in patients with SSc (29.8±40.7 pg/ml) were significantly higher than in healthy controls (13.0±24.8 pg/ml, (p=0.03) while they were similar to those of patients with VEDOSS (22.6±21.7 pg/ml). Plasma levels of IL-6 were higher in SSc patients (5.7±11.1 pg/ml) compared to VEDOSS (1.5±1.2 pg/ml) (p=0.04), RP (1.1±0.5 pg/ml), (p<0.0001) and healthy controls (1.9±3.1 pg/ml) (p<0.001). Levels of VEGF-R2 and sIL-6R were comparable in all groups. IL-6 levels were higher in dcSSc patients than in lcSSc patients (7.9±13.0 pg/ml vs 1, 9±0, 6 pg/ml) (p=0, 0027). Finally in patients with SSc the capillaroscopic density inversely correlated with the levels of IL-6, the Activity and Severity Indices, the Skin Score and the duration of the disease. Conclusions: An impairment of FMD was present in patients with RP, in particular in SSc and VEDOSS patients, suggesting a contemporary impairment of microvascular and macrovascular compartments. The deeper FMD impairment that characterize either SSc and VEDOSS patients, suggests that the endothelial dysfunction is already established since the early phases of the disease and it worses during the disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4446